Quality Systems in the Food Industry - Fiorino, Marco; Barone, Caterina; Barone, Michele; Mason, Marco; Bhagat, Arpan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book explains the role of food-oriented (or 'food-centric') quality system standards in the modern food and beverage industry. It discusses food safety schemes based on the international norm ISO 9001 and the "Hazard Analysis and Critical Control Points" approach, and also introduces the new Global Standard for Food Safety (GSFS) and the International Featured Standard (IFS, 7th ed.), outlining standardization for international equivalence (while maintaining the necessary flexibility and independence - which is not always easy an easy task). Providing selected specific examples, it examines the problems of chemical additives and possible cross-contaminations between different production lines, as well as adequate reactions to and handling of intentional adulterations. In addition, it includes a chapter focusing on quality audits and technical data sheets in the food industry, and a final chapter describing the certification of food-grade lubricants in the food industry, especially with regard to allergenic substances.
Impact of Food-related Quality System Certifications for Chemical Food Additives -- Chemical Aspects of Intentional Food Adulteration and Quality Management Systems -- Quality Audits in Food Companies and the Examination of Technical Data Sheets -- Allergen Risks and the Use of Certified Lubricants in the Modern Food Industry.
Keywords: Food science; Security systems; Nutrition .; Food Science; Security Science and Technology; Nutrition